2020
DOI: 10.1038/s41598-020-74451-9
|View full text |Cite
|
Sign up to set email alerts
|

Transpapillary tissue sampling of biliary strictures: balloon dilatation prior to forceps biopsy improves sensitivity and accuracy

Abstract: The early and definitive diagnosis of malignant bile duct stenoses is essential for a timely and adequate therapy. However, tissue sampling with transpapillary brush cytology (BC) or forceps biopsy (FB) remains challenging. With this study, we aimed to compare the effectiveness and safety of different tissue sampling modalities (BC, FB without/after previous balloon dilatation). Standardized database research identified all patients, who underwent endoscopic retrograde cholangiography with BC and/or FB for ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…As was the case in this study, intrinsic stenosis is more frequently proximal than distal 22 . As previous biliary stricture dilation 23 24 25 or biliary aspiration 26 27 may optimize the sensitivity of brushing, we proposed performing these procedures during ERCP. Such optimization of the standard brushing via previous biliary stricture dilation or biliary aspiration could explain the relatively high sensitivity rate of 67 % with the standard RX Cytology Brush in this study.…”
Section: Discussionmentioning
confidence: 99%
“…As was the case in this study, intrinsic stenosis is more frequently proximal than distal 22 . As previous biliary stricture dilation 23 24 25 or biliary aspiration 26 27 may optimize the sensitivity of brushing, we proposed performing these procedures during ERCP. Such optimization of the standard brushing via previous biliary stricture dilation or biliary aspiration could explain the relatively high sensitivity rate of 67 % with the standard RX Cytology Brush in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Several techniques in tissue sampling have been shown to improve the diagnostic accuracy of ERCP-based tissue sampling. Balloon dilatation of the biliary stricture prior to forcep biopsy improved the sensitivity from 40% to 71% and was not associated with a higher complication rate [12]. In a pilot study, post-brushing biliary lavage fluid cytology by injecting 5-15 mL of saline into the bile duct after brushing improved the cumulative sensitivity by 24% [13].Fluorescence in situ hybridization (FISH) has been used to measure the DNA content of potential oncogenic genes on brush cytology samples for over a decade.…”
Section: Cholangiogram Appearance Brush Cytology and Transpapillary B...mentioning
confidence: 93%
“…Several techniques have been proposed to enhance tissue acquisition during ERCP, such as the use of novel brushes, biliary stricture dilation followed by biopsies and brushing, and repetitive brushings. Pörner et al [ 9 ] have suggested that balloon dilation of the stricture before forceps biopsies can improve sensitivity from 40% to > 70% without increasing the complication rate. In another study by Sugimoto et al [ 10 ] post brushing biliary lavage fluid was obtained by injecting small amount of saline into bile duct.…”
Section: Endoscopic Management Of Idbssmentioning
confidence: 99%